Gastric-filling ultrasonography to evaluate gastric motility in patients with Parkinson's disease - Zou, Xianwei; Chen, Xiaqing; Wen, Yanxia; Jing, Xiaofeng; Luo, Man; Xin, Fengyue; Tang, Yao; Hu, Mengfei; Liu, Jian; Xu, Fan (Frontiers in Neurology, 2024)
Background Delayed gastric emptying is a common non-motor symptom of Parkinson's disease (PD). However, there is currently no objective evaluation and diagnostic method for this condition. Objectives The purpose of this study was to evaluate the feasibility of gastric-filling ultrasonography for gastric motility in patients with PD and the relationship between gastric dynamics and gastrointestinal symptoms and motor symptoms of PD. Design, setting, and patients We performed a case-control study with 38 patients with PD and 34 healthy controls. Methods All patients underwent a 120-min ultrasonography examination using a 500-ml semi-liquid test meal. We determined the antral contraction amplitude (ACA), the antrum contraction frequency (ACF), the motility index (MI), and the gastric antral cross-sectional area (CSA). We acquired the CSA at six time points: fasting for 12 h (T0), immediately after drinking the semi-liquid test meal (T1); and at 30 (T30), 60 (T60), 90 (T90), and 120 (T120) min. We calculated the gastric emptying rate (GER) at different time points by using the CSA. We compared the GER between the groups and evaluated the correlation between the GER and gastrointestinal symptoms and motor symptoms of PD. Results The MI and ACF were significantly lower in the PD group compared with the control group (P < 0.05). The GER at T30 and the ACA showed no significant difference between the groups (P > 0.05). At different time points, the GER was significantly different between the PD and control groups (P < 0.001). There was no significant association between the GER and gastrointestinal symptoms; none of them were risk factors for impaired gastric emptying (odds ratio > 1). The GER was negatively correlated with the severity of PD motor symptoms (P < 0.05). Conclusion Patients with PD had significantly delayed gastric emptying, which was negatively correlated with the severity of PD motor symptoms. Measuring gastric emptying by gastric-filling ultrasound had good diagnostic value in clinical screening for delayed gastric motility in patients with PD. Clinical Trial Registration https://www.chictr.org.cn/showproj.html?proj=126304.